Curing kinetics of bio‐based epoxy resin based on epoxidized soybean oil and green curing agent. Issue 1 (22nd September 2016) - Chen, Yahua; Xi, Zhenhao; Zhao, Ling
Abstract : New thermoset with a high bio‐based content was synthesized by curing epoxidized soybean oil (ESO) with a green curing agent maleopimaric acid catalyzed by 2‐ethly‐4‐methylimidazole. Non‐isothermal differential scanning calorimetry and a relatively new integral isoconversional method were used to analyze the curing kinetic behaviors and determine the activation energy (Ea ). The two‐parameter Šesták–Berggren autocatalytic model was applied in the mathematical modeling to obtain the reaction orders and the pro‐exponential factor. For anhydride/epoxy group molar ratio equal to 0.7, Ea decreased from 82.70 to 80.17 kJ/mol when increasing the amount of catalyst from 0.5 to 1.5 phr toward ESO. The reaction orders m and n were 0.4148 and 1.109, respectively. The predicted non‐isothermal curing rates of Šesták–Berggren model matched perfectly with the experimental data. © 2016 American Institute of Chemical Engineers AIChE J, 63: 147–153, 2017